Certain Environmental Conditions Maximize Ammonium Accumulation and Minimize Nitrogen Loss During Nitrate Reduction Process by Pseudomonas putida Y-9 - Huang, Xuejiao; Tie, Wenzhou; Xie, Deti; Jiang, Daihua; Li, Zhenlun (Frontiers in Microbiology, 2021)
Realizing the smallest nitrogen loss is a challenge in the nitrate reduction process. Dissimilatory nitrate reduction to ammonium (DNRA) and nitrate assimilation play crucial roles in nitrogen retention. In this study, the effects of the carbon source, C/N ratio, pH, and dissolved oxygen on the multiple nitrate reduction pathways conducted by Pseudomonas putida Y-9 are explored. Strain Y-9 efficiently removed nitrate (up to 89.79%) with glucose as the sole carbon source, and the nitrogen loss in this system was 15.43%. The total nitrogen decrease and ammonium accumulation at a C/N ratio of 9 were lower than that at 12 and higher than that at 15, respectively (P<0.05). Besides, neutral and alkaline conditions (pH 7–9) favored nitrate reduction. Largest nitrate removal (81.78%) and minimum nitrogen loss (10.63%) were observed at pH 7. The nitrate removal and ammonium production efficiencies of strain Y-9 increased due to an increased shaking speed. The expression patterns of nirBD (the gene that controls nitrate assimilation and DNRA) in strain Y-9 were similar to ammonium patterns of the tested incubation conditions. In summary, the following conditions facilitated nitrate assimilation and DNRA by strain Y-9, while reducing the denitrification: glucose as the carbon source, a C/N ratio of 9, a pH of 7, and a shaking speed of 150 rpm. Under these conditions, nitrate removal was substantial, and nitrogen loss from the system was minimal.